The most important challenges facing higher education in Libya, Al-mergib University as a model (Al-Qalaa Journal, 2024)
It is clear that the most important issues in developing countries are the excellence and quality of the national education Several escalating challenges are those which are relating to the faculties administrations. These are responsible for poor administrative and academic performance. In addressing those challenges, faculty deans and administrators are expected to take full accountability for the implementations of the education policies into practice efficiently. Thus, management in education relates to the operations of the educational organizations. It includes three aspects: planning, organizing, and directing the activities in an institution effectively. It also means the use of   humans and different resources in order to make the institutions achieve its goal. Thus, to make the university achieve its objectives, it should have these departments. They are:(1) Human Resource Management (HRM), (2) Operation Management (OM), (3) Strategic Management(SM),(4) Marketing Management(MM),(5) Financial Management (FM),(6)  and Information Technology(IT). So this paper will shed light on Education in Libya and its importance  for developing and sustaining human being. However, Education in Libyan faces massive problems especially in funding. This is simply because education is free for every Libyan person from primary school which is compulsory to university. This causes big burden on the budget. This of course leads to make the ranking go up and down depending on the amount of funding the government give to these institutions